DIGITAL EMPOWERMENT OF TEACHERS: CHALLENGES AND OPPORTUNITIES IN THE 21ST-CENTURY LEARNING ECOSYSTEM - Rathore, Suman; Sharma, Sapna (International Journal of Research -GRANTHAALAYAH, 2025)
The rapid advancement of digital technologies has significantly transformed contemporary education systems, redefining the teaching-learning process and professional roles of teachers. In this context, digital empowerment of teachers has emerged as a crucial requirement for strengthening the 21st-century learning ecosystem. Digital empowerment enables teachers to confidently and effectively integrate technological tools for instruction, assessment enables teachers to confidently and effectively integrate technological tools for instruction, assessment, communication, and professional development. Despite the growing availability of digital resources, teachers continue to face several challenges, including inadequate digital infrastructure limited digital resources, teachers continue to face several challenges, including inadequate digital infrastructure, limited digital competence, resistance to technological change, increased professional workload, and insufficient institutional support. This paper is conceptual in nature and is based on an analytical review of existing literature, educational policies, and scholarly studies. It critically examines the concept of digital empowerment of teachers, analyses key challenges hindering its effective implementation, and explores the opportunities offered by digital technologies in education. The paper concludes that sustained teacher training, improved infrastructure, and supportive educational policies are essential for achieving meaningful and sustainable digital empowerment of teachers in the 21st century.